Komodifikasi Informasi Kesejarahan Raja Udayana sebagai “Heritage Tourism” - I Made Sendra (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
This articles analyses historical information commodification of Udayana King and his wife, Guna Priya Dharmapatni who governed Bali in the 12th century. The purpose of this study is to understand the profile and role of Udayana King and his wife in the era of the ancient history of Bali through global discourse of heritage tourism. The archeological and historical data related to the king and queen will be composed to be historical tourism package by utilizing the visual image of metaphor and the semiotic language of tourism. The research shows that the accuracy of information package could be quantified through the excogitation of tourist’s gaze. The tourism gaze is connected to how the guest interprets the information which is narrated by tour guide and takes some understanding from the local history and wisdom.